Determination and correlation of matrix metalloproteases profile and total antioxidant capacity in severe early childhood caries children - A randomized clinical trial - Umapathy Thimmegowda; K Soumya Pai (Wolters Kluwer Medknow Publications, 2023)
Background and Objective: Matrix metalloproteinases (MMPs) are a multigene family that belongs to the metalloproteinase class of endopeptides, responsible for the remodeling and degeneration of extracellular matrix molecules. MMPs are collectively called Matrixins are known to participate in tooth development and dentin-caries progression. Total antioxidant capacity (TAC) is the measure of the amount of free radicals scavenged by a test solution, being used to evaluate the antioxidant capacity of biological samples. Oxidative stress can affect the initiation and progression of many inflammatory and infectious diseases such as dental caries. Early childhood caries (ECC) is a serious public health problem that adversely affects children's physical and mental health. Aim: The study aims to investigate and correlate the presence of MMPs and TAC in saliva of children with ECC. Materials and Methods: The present study was done on 50 children aged 3-6 years with severe ECC. Unstimulated, whole saliva samples were collected and stored and all 50 samples were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis to determine MMPs and were subjected to spectrometry to assess the TAC of saliva. The samples with the presence of MMPs and increased TAC values were subjected to liquid chromatography-mass spectrometry to check the correlation of MMPs and TAC in ECC. Results: TAC was 0.81 ± 0.14 mmol/l in the caries-active group and 0.15 ± 0.05 mmol/l in the caries-free group and was statistically significant at P < 0.001. MMP level in the caries-active group was 715.75 ± 102.42 μg/ml, whereas, in the caries-free group, it was 250.89 ± 86.51 μg/ml and was statistically significant at P < 0.001. The salivary MMP and TAC levels showed a significant positive moderate correlation with caries scores in the caries-active group and the finding was statistically significant at P < 0.001. Conclusion: From our results, it can be concluded that the both MMPs and TAC levels were high in caries active group than in the caries-free group. The salivary MMPs showed a moderate positive correlation with TAC in the ECC group. In age-wise comparison, the mean MMP levels in the caries active group were higher in children between 3 and 4 years than in 5-6 years. In the caries-free group, the mean MMP level was similar in both the age groups.